2019
DOI: 10.1159/000501187
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Dopamine Receptors in Immune Regulatory Cells

Abstract: <b><i>Objective:</i></b> Parkinson’s disease (PD) patients are usually treated with L-dopa and/or dopaminergic agonists, which act by binding five types of dopaminergic receptors (DRD1–DRD5). Peripheral immune cells are known to express dopamine receptors on their membrane surface, and therefore they could be directly affected by the treatment. Regulatory cells are the main modulators of inflammation, but it is not clear whether dopaminergic treatment could affect their functions. While… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Interestingly, the regions with the highest clozapine levels are known to express a high density of DR1 and DR2, and the cerebellum, with low dopamine levels, has lower DR expression 54 . All DRs are reported to be widely expressed in the CNS and several studies have reported their expression on immune cells 11 , which play an important role in MS 50 . Moreover, DR expression on immune cells is also associated with some neurological and immune-related disorders 55,56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the regions with the highest clozapine levels are known to express a high density of DR1 and DR2, and the cerebellum, with low dopamine levels, has lower DR expression 54 . All DRs are reported to be widely expressed in the CNS and several studies have reported their expression on immune cells 11 , which play an important role in MS 50 . Moreover, DR expression on immune cells is also associated with some neurological and immune-related disorders 55,56 .…”
Section: Discussionmentioning
confidence: 99%
“…Clozapine antagonises dopamine receptors (DR), which can be separated into two subtypes, D1 subtypes (DR1 and DR5) and D2 subtypes (DR2, DR3 and DR4), based on modulation of cAMP production 10 . All DRs are highly expressed in the brain 10 and on immune cells 11 , and have shown to be involved in mental disorders and neuroinflammatory diseases like schizophrenia, depression, Parkinson's and Huntington's disease 12,13 . Given clozapine's affinity for DRs, it has been reported to displace dopamine from the receptor within less than one minute 14,15 , directing it towards other receptors and causing it to have unanticipated effects.…”
mentioning
confidence: 99%
“…A number of catecholamine family members, including dopamine, have been extensively involved in the regulation of the immune response (Tracey, 2009), affecting both the innate and adaptive immune system (Pacheco et al, 2014;Vidal and Pacheco, 2019). In this regard, dopamine receptors are expressed on T and B lymphocytes, dendritic and NK cells, macrophages, microglia, intermediate monocytes, neutrophils, and eosinophils (Levite, 2016;Arce-Sillas et al, 2019). In this section we focused in the analysis of the dopaminergic regulation of T cells, microglia, and monocytes, since these immune cells have been implicated in cognitive functions.…”
Section: Dopaminergic Regulation Of the Immune Systemmentioning
confidence: 99%
“…Accordingly, treatment of primary microglial cultures with a DRD2/DRD3 agonist, increases the release of nitrite and IFN-γ [ 162 ]. Dopamine receptors are also expressed on dendritic cell, on natural killer (NK) cells, macrophages, microglia, intermediate monocytes, neutrophils, and eosinophils [ 163 ]. All these immune cells participate to both cognitive functions and the modulation of glioma microenvironment thus, these data highlight additional putative immunomodulatory roles of dopamine signaling [ 164 , 165 , 166 ].…”
Section: Neurotransmitters Beyond the Neuronal Functionmentioning
confidence: 99%